Religious Education for Sheikh Muhammad Jalizadeh: Mullah Al-Kabir - Hawar Samad Ahmed; Hemin Aziz Braem (QALAAI ZANIST JOURNAL, 2024)
The vastness of the world, the rapid spread of information, the multiplicity of educations, civilizations, and positivist and material ideas, and thus the ease of influence of what comes to the children of Muslims from the eastern and western trends, obliges us to stand in a corner that enables us to see the correct vision of education, and this is only by referring to the legacy of the righteous predecessors of Muslim scholars in the field of education because they derive Their ideas are from the original Islamic sources, and they promoted Islamic civilization to be the strongest civilization in those ages. Returning to the Islamic heritage and to the achievements of Muslim scholars would enlighten those in charge of education in general in Islamic societies and lead them to prepare the true Muslim who is distinguished by his personality and thought. Sheikh Jalizadeh had clear contributions in the field of educational knowledge, and he came out to us with an original, broad, comprehensive, and renewable educational thought that searches for knowledge in every field without being limited to one source or a specific framework, starting from the basic sources of the Book, the Sunnah and the mind. Educational knowledge came from Sheikh Jalizadeh is scattered in his multiple books, so that it is difficult to classify a man's thought within a specific science of educational sciences, as he broadcast many educational ideas and opinions in parts of books; The educational knowledge of Sheikh Jlizadeh contained opinions on educational psychology and mental health. Religious education, learning and its theories, educational sociology, philosophy of education... Then: This research aims to identify the importance of education for Sheikh Muhammad Jalizadeh through his ideas and valuable references in his writings.